Correlates of bushmeat in markets and depletion of wildlife. Issue 3 (7th January 2015) - Fa, John E.; Olivero, Jesus; Farfán, Miguel Á.; Márquez, Ana L.; Duarte, Jesús; Nackoney, Janet; Hall, Amy; Dupain, Jef; Seymour, Sarah; Johnson, Paul J.; Macdonald, David W.; Real, Raimundo; et al.
Abstract We used data on number of carcasses of wildlife species sold in 79 bushmeat markets in a region of Nigeria and Cameroon to assess whether species composition of a market could be explained by anthropogenic pressures and environmental variables around each market. More than 45 mammal species from 9 orders were traded across all markets; mostly ungulates and rodents. For each market, we determined median body mass, species diversity (game diversity), and taxa that were principal contributors to the total number of carcasses for sale (game dominance). Human population density in surrounding areas was significantly and negatively related to the percentage ungulates and primates sold in markets and significantly and positively related to the proportion of rodents. The proportion of carnivores sold was higher in markets with high human population densities. Proportion of small‐bodied mammals (<1 kg) sold in markets increased as human population density increased, but proportion of large‐bodied mammals (>10 kg) decreased as human population density increased. We calculated an index of game depletion (GDI) for each market from the sum of the total number of carcasses traded per annum and species, weighted by the intrinsic rate of natural increase (rmax) of each species, divided by individuals traded in a market. The GDI of a market increased as the proportion of fast‐reproducing species (highest rmax) increased and as the representation of species with lowest rmax (slow‐reproducing) decreased. The best explanatory factor for a market's GDI was anthropogenic pressure—road density, human settlements with >3000 inhabitants, and nonforest vegetation. High and low GDI were significantly differentiated by human density and human settlements with >3000 inhabitants. Our results provided empirical evidence that human activity is correlated with more depleted bushmeat faunas and can be used as a proxy to determine areas in need of conservation action.